Pengaruh Model Inquiry-Based Learning terhadap Kemampuan Berpikir Kreatif Peserta Didik: Literature Review - Kidaningsih, Marisya; Fitri, Rahmadhani (Al-Alam: Islamic Science Education Journal, 2025)
Creative thinking skills are one of the important competencies in 21st-century learning that need to be developed in students. This study aims to analyze the effect of the Inquiry-Based Learning (IBL) model on students' creative thinking skills. This article uses a literature review approach to analyze the effect of the Inquiry-Based Learning (IBL) model on students' creative thinking skills. This approach was chosen because it allows for an in-depth synthesis of various current literature sources. Data were collected through a systematic search of leading academic databases such as Google Scholar and ScienceDirect for the period 2015-2025. The results of the analysis show that the application of the Inquiry-Based Learning (IBL) model consistently has a positive and significant effect on improving students' creative thinking skills. This review is limited to eight articles, which may not fully represent the broader scope of research implementation in various educational contexts. Future research is expected to integrate a larger and more diverse collection of sources.